Gambaran Penanganan Status Gizi Balita di Wilayah Kerja Puskesmas Jagir Surabaya - Jihan Ekanita Anwar; Akas Yekti Pulih Asih; Aviana Gita Lara (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Based on data from the World Health Organization (WHO) in 2017, more than half of the deaths of children under five years are caused by diseases that can be prevented and treated by easy and affordable interventions. The prevalence of wasting under five according to the Indonesian Nutritional Status Survey (2022) in the city of Surabaya is 6.1%. The wasting rate in the city of Surabaya is below the national and provincial averages. Meanwhile, the prevalence of underweight toddlers in the city of Surabaya is 7.5%, this prevalence rate is below the average prevalence of East Java Province, which is 15.8%. Descriptive research with retrospective design, using accidental sampling. In January and February, nutritional status in the normal category had the highest percentages, namely 80.86% and 82.26%. Interventions carried out by health workers resulted in a decrease in the percentage of malnutrition in February by 0.11%. The risk of over nutrition decreased by 1.12%, in nutritional status in the category of overweight and obesity there was also a decrease of 0.04% and 0.37%. Handling programs in reducing malnutrition rates in toddlers, namely monitoring weight and height / body length through home visits, giving milk (CFC), giving KIE to family members, coordinating with cross-sectors if there are obstacles related to non-health problems, there are a decrease in malnutrition status from 4 (0.15%) toddlers in January 2023 to 1 (0.036%) toddlers in February 2023, so that the numbers found are below the minimum target of 1.8% malnutrition rate of the total toddlers examined. The factor of malnutrition is due to congenital abnormalities or what is commonly called a congenital disease.